2023
DOI: 10.1111/age.13291
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for, and genetic association with, intestinal atresia in dairy calves

Abstract: Intestinal atresia is a congenital defect, found in a wide variety of species, that results in complete occlusion of the intestinal lumen (Ducharme et al., 1988). The occlusion can occur in the duodenum, jejunum, ileum, colon, or anus, and prevents the normal movement of gut contents and the passing of faecal material. In calves, common presentations include failure to pass meconium and faeces, inappetence and abdominal distension; affected animals usually die within 7 days of birth or are euthanised (Mee, 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…While the number of cases of intestinal atresia recorded here was limited, it did suggest that calves from pluriparae and males were more commonly affected. These trends are borne out by a recent Irish study of 197 cases which found that both pluriparity and male gender were significant risk factors (Keane et al., 2023). As with schistosomus reflexus, this indicates that preventive measures are warranted at a national/supra‐national level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the number of cases of intestinal atresia recorded here was limited, it did suggest that calves from pluriparae and males were more commonly affected. These trends are borne out by a recent Irish study of 197 cases which found that both pluriparity and male gender were significant risk factors (Keane et al., 2023). As with schistosomus reflexus, this indicates that preventive measures are warranted at a national/supra‐national level.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly diagnosed bovine congenital defect has variously been attributed to umbilical hernia (Čítek et al., 2009) or arthrogryposis (Bähr & Distl, 2005). The only Irish studies conducted on intestinal atresia have estimated that it occurs in 0.3%–0.4% of all dairy calves born and in up to 25% of herds (Keane et al., 2023; Mee, 1994). The top ranking of atresia in this study reflects its two common clinical presentations, veterinary‐assisted dystocia and a call out to examine/kill a calf that has become anorexic, bloated, in pain and is not passing faeces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Good herd nutritional and health management reduces risks from these factors. However, the primary preventive focus is on preventing heritable genetic defects via national genetic monitoring programmes by genotyping AI sires to detect carriers for deleterious alleles to prevent recessively inherited defects (Keane et al, 2023).…”
Section: Preventionmentioning
confidence: 99%